On the Effectiveness of Group Dialectical Behavior Therapy in the Enhancement of Distress Tolerance and Emotional Regulation in Substance Abusers - mohsen nadimi (Research on Addiction, 2016)
Objective: The aim of this study was to investigate the effectiveness of group dialectical behavior therapy in the improvement of distress tolerance and emotion regulation among substance abusers. Method: A quasi-experimental study along with pretest-posttest and control group was used for the conduct of this study. The population of the study consisted of all addicts referring to addiction treatment center of Zahedshahr (Omid Center) in summer 2012. From among this population, the number of 28 addicts was selected via convenience sampling as the participants of the study and was randomly assigned to two experimental and control groups. The participants responded to Difficulties in Emotion Regulation Scale and Distress Tolerance Scale as pretest, posttest, and follow-up test. The experimental group received group dialectical behavior therapy for 20 one-hour sessions whereas the control group received only Naltrexone drug. Results: The results showed that dialectical behavior therapy was effective in increasing distress tolerance and emotion regulation in substance abusers. Conclusion: Dialectical behavior therapy training can improve distress tolerance and emotion regulation, which could be the main reason for the continued use of drugs.